Ketidakpastian Tugas Sebagai Variabnel Moderasi Dalam Hubungan Antara Dimensi Kemanfaatan Teknologi Informasi Dan Kepuasan Pamakai - Fauziyah, Fauziyah; Agusti, Tiara Kumala (Universitas Muhammadiyah Yogyakarta, 2010)
This study explains how the utilization of the information technology influences the end-user computing satisfaction. This study also examines the information effect between task uncertainly and dimantion of utilization information technology insist the delivery and the scope of the utilization.Purposive sampling is used for taking samples. The samples are structural official in the goverment city of Yogyakarta that used management information system to their daily job. Multiple regression is used to examine the influence of the dimension of utilization on end-user computing satisfactiomns.While, to exam-ine the interaction effect between task uncertainly and dimension of utilization on end-user computing satisfactions used Moderated Regression Analysis (MRA).The result shows that dimension of utilization are influence on end-user computing satisfactions. But the interaction between task uncertainly and dimension of utilization are not influence significantly.